Anatolian endemic genus Bolua (Orthoptera: Tettigoniidae: Tettigoniinae): genetic and phenotypic data indicate inconsistent diversity and evolutionary patterns - Uluar, Onur; Yahyaoğlu, Özgül; Çiplak, Battal (Zootaxa, 2022)
Anatolia harbours diverse and unique biodiversity. Nearly half of the genera and more than 80% of the species belonging to the tettigoniid subfamily Tettigoniinae are endemic to Anatolia. Although the Anatolian Tettigoniinae have been well studied, proper documentation of Tettigoniinae biodiversity requires studies using contemporary approaches and techniques. We attempted to study the taxonomy, phylogeny, and phylogeography of the Bolua, a monotypic genus endemic to northwest Anatolia. Species delimitation tests applied to three mitochondrial and two nuclear gene segments indicated three putative species in the genus. Analyses suggested inversely related genetic and phenotypic divergence. By integrating these results, we reached the following conclusions. (i) The plausible taxonomic composition recognizes three species in the genus; the type species Bolua turkiyae and two new species B. balikesirensis sp. n. and B. bursaensis sp. n., (ii) the radiation steps in Bolua correspond to the starting of the Pliocene, Mid Pleistocene Transition (MPT) and end of cold periods of Günz and Riss glacial. By considering intra generic divergence steps and habitat preference plus the distribution pattern of the species, ecological speciation seems to be the mode of generic radiation, (iii) possibly due to habitat conservatism, the isolated relict populations on highlands evolved under similar selection pressures, and this led to a conserved phenotype, consequently morphologically poorly diverged species, though genetic divergence is deep and (iv) although morphological diagnoses is poor, genetic divergence between species is deep, and each species fulfils the criteria of several species concepts.